Publisher Correction: MethCORR modelling of methylomes from formalin-fixed paraffin-embedded tissue enables characterization and prognostication of colorectal cancer - Trine B. Mattesen (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.